2011
DOI: 10.1089/cap.2010.0139
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Pilot Study of Adjunctive Olanzapine for Adolescents with Anorexia Nervosa

Abstract: These preliminary findings do not support a role for adjunctive olanzapine for underweight adolescent females with anorexia nervosa-restricting type who are receiving standard care in an eating disorder treatment program (clinical trials.gov; no. NCT00592930).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 15 publications
5
111
1
4
Order By: Relevance
“…There is no evidence to suggest that pharmacotherapy in AN should be first line, but it may play a role in individual patients resistant to treatment or with premorbid psychiatric conditions. 107,[128][129][130] In BN, several RCTs in adults have found that antidepressants are effective in decreasing binge eating and purging symptoms. Specifically, fluoxetine has a strong evidence base and is approved by the Food and Drug Administration for use in adults with BN; thus far there is some evidence that the effects are similar in adolescents.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…There is no evidence to suggest that pharmacotherapy in AN should be first line, but it may play a role in individual patients resistant to treatment or with premorbid psychiatric conditions. 107,[128][129][130] In BN, several RCTs in adults have found that antidepressants are effective in decreasing binge eating and purging symptoms. Specifically, fluoxetine has a strong evidence base and is approved by the Food and Drug Administration for use in adults with BN; thus far there is some evidence that the effects are similar in adolescents.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…The updated literature search yielded 698 citations in the initial search step and finally, six citations on four trials were incorporated [31,32,33,34]. Online supplementary figure 1 (see www.karger.com/doi/10.1159/000369978 for all online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…In those studies indicating the subtype of anorexia nervosa 64.2% suffered from the restricting subtype and the remaining ones from the binge-purging subtype. Four trials examined an antipsychotic medication with olanzapine (n = 112) [28,29,31,33], two with quetiapine (n = 48) [30,34], and one with risperidone (n = 41) [32]. All studies were characterized by a parallel-group design.…”
Section: Resultsmentioning
confidence: 99%
“…Two (Kafantaris 2011;Norris 2011) showed no greater benefit of olanzapine over placebo. Similarly, a randomised trial of risperidone v. placebo found no effect on eating disorder rating scales or weight (Hagman 2011).…”
Section: Treatment Of Anorexia Nervosamentioning
confidence: 92%